Extension of the commitment clause in contracts Affiliates - Amari, Marina (2022)
The article analyzes the relationship between related contracts and arbitration clause. The central idea of the discussion is to verify if it is possible extend the arbitration clause contained in one of the contracts to another related contract that does not predict the submission of the dispute to arbitration. The work analyzes the doctrinal productions about the coalition, addressing are the causes for which such phenomenon occurs, and explaining the importance of a systematic interpretation of the coalition, a legal institute that takes into account the contractual cause. The article addresses the main characteristics of the arbitration clause, autonomy and consensualism, seeking to demonstrate how it would be possible to allow the extension of the arbitration clause even though the provision of the Arbitration Law that such agreement must be written (art. 4º, § 1º). At the end, two relevant cases on the subject judged by the Superior of Justice were analyzed. The methodology used was doctrinal research in comparison with a jurisprudential analysis, the latter from a qualitative choice. Based on the results obtained, the relevant and guiding elements for the solution of the problem of extending the arbitration clause to related contracts were identified.